EATING PATTERN CONTAINS EXCESSIVE PURIN SUBSTANCE IMPROVING GOUT ARTHRITIS PREVALENCE IN COMMUNITIES IN KOTABUNAN VILLAGE - Rizky Nurul Fauziah; Herlina P Memah; Lorrien G Runtu (Jurnal Ilmiah Perawat Manado (Juiperdo), 2018)
Background: Gout Arthritis is an inflammatory disease in the joints that causes extreme pain, swelling, sometimes redness and is difficult to move and if it lasts for a long time it can cause deformity in the affected joint. Objective: To determine the relationship between diet and gout arthritis. The design used is correlation. Method: This type of research is analytic descriptive research with cross-sectional approach. the location of the study was in Kotabunan Village, Kotabunan Subdistrict, Bolaang Mongondow Timur Regency from July 21 to July 23, 2018. The sampling technique used a total sample with 49 respondents. The instrument uses a food recall questionnaire 2 x 24 hours. Results: Statistical test with chi-square with significance level (α) 0.05. Correlation test results obtained ρ = 0.002. The conclusion : This study is that there is a relationship between diet and the incidence of gout arthritis, where the more often the consumption of high purine content, the higher the value of uric acid levels. Suggestion: People can maintain their diet well considering there are still many people who do not maintain their diet so that it results in increased levels of uric acid in the blood.